Implementasi Hybrid ANP-TOPSIS untuk Evaluasi Pembinaan Narapidana (Studi Kasus: Lapas XYZ) - Muhamad Haykal Muktabar; Hadi Zakaria (STMIK Banjarbaru, 2026)
The evaluation of inmate rehabilitation at XYZ Prison is still conducted manually, which has the potential to introduce subjectivity and complicates the management of historical data needed for decision-making regarding remission recommendations. This study aims to implement a web-based decision support system to improve the objectivity and consistency of inmate rehabilitation evaluations. The system was developed by combining the Analytic Network Process method to determine subcriteria weights and the Technique for Order Preference by Similarity to Ideal Solution to rank alternatives based on rehabilitation outcomes. The system was implemented using the PHP programming language and a MySQL database. The results show that the system successfully generated a ranking of eight inmate alternatives based on preference scores, as well as parole recommendations in accordance with predetermined thresholds. Performance testing of the method using the Accuracy, Precision, and Recall metrics showed a good level of alignment between the system’s recommendations and the decisions of the Correctional Monitoring Team. The resulting system is capable of supporting the rehabilitation evaluation process in a more objective, structured, documented, and transparent manner to aid decision-making. Keywords: Decision Support System; Analytic Network Process; Technique for Order of Preference by Similarity to the Ideal Solution; Evaluation of Inmate Rehabilitation; Sentence Reduction Abstrak Evaluasi pembinaan narapidana di Lapas XYZ masih dilakukan secara manual sehingga berpotensi menimbulkan subjektivitas dan menyulitkan pengelolaan data historis yang diperlukan dalam pengambilan keputusan rekomendasi remisi. Penelitian ini bertujuan mengimplementasikan sistem pendukung keputusan berbasis web untuk meningkatkan objektivitas dan konsistensi evaluasi pembinaan narapidana. Sistem dikembangkan dengan mengombinasikan metode Analytic Network Process untuk menentukan bobot subkriteria dan Technique for Order Preference by Similarity to Ideal Solution untuk melakukan pemeringkatan alternatif berdasarkan hasil pembinaan. Implementasi sistem dilakukan menggunakan bahasa pemrograman PHP dan basis data MySQL. Hasil penelitian menunjukkan bahwa sistem berhasil menghasilkan pemeringkatan delapan alternatif narapidana berdasarkan nilai preferensi serta rekomendasi remisi sesuai ambang batas yang telah ditetapkan. Hasil pengujian kinerja metode menggunakan metrik Accuracy, Precision, dan Recall menunjukan tingkat kesesuaian yang baik antara rekomendasi sistem dan keputusan Tim Pengamat Pemasyarakatan. Sistem yang dihasilkan mampu mendukung proses evaluasi pembinaan secara lebih objektif, terstruktur, terdokumentasi, dan transparan dalam mendukung pengambilan keputusan. Kata kunci: Sistem Pendukung Keputusan; Analytic Network Process; Technique for Order Preference by Similarity to Ideal Solution; Evaluasi Pembinaan Narapidana; Remisi